An axiomatization of the inner core using appropriate reduced games - Geoffroy de Clippel (Brown University, Department of Economics, 2005)
I adapt a reduction process introduced by Serrano and Volij (1998) so that the reduced games of convex-valued games are convex-valued. I use the corresponding consistency property and its converse to axiomatize the inner core for games that are convex-valued, non-level and smooth.
Keywords: 330; Core; Spieltheorie